PEMBELAJARAN BAHASA ARAB (MANAJEMEN MENUJU OUT PUT BERKWALITAS) - Hani’atul Khoiroh (Al-Fakkaar, 2020)
Management is a pillar in carrying out all activities both economic, social and educational. In the world of education, especially in the learning process, management becomes an important foundation in teaching and learning activities so that the process carried out reaps the desired output. In the process of human learning, it is not only the desired outcome but the process is also important because it is the process that leads to the achievement of learning. As for learning Arabic there are many problems that must be solved, both linguistic and non-linguistic problems. all of that must be found a solution so that the expected output can be achieved optimally. One solution that can be applied is to manage the learning process as well as possible. While this paper, which wants to uncover the concept of learning Arabic which can later be implemented to overcome the problems faced in various schools both public and private. Management of Arabic learning itself is a management of important components of learning that are arranged in a comprehensive manner starting from planning, organizing, mobilizing, and evaluating to achieve the expected learning objectives. In the management of Arabic learning that must be considered are the four learning principles, namely, the principle of priority (Al-Uluwyyat), the principle of corrective (Ad Diqqoh), the principle of tiered (Ad Darjiyyah) and the principle of longing for learning (At-Tasywiq). The procedures that must be carried out are, firstly planning (plan), namely planning for teachers, students, class or learning environment and curriculum (syllabus and learning implementation plan), secondly implementing (do), ie carrying out from what was planned, thirdly monitoring ( check) ie the learning process is overseen by the GA team, which later when a learning problem is found then it can be consulted to the team that has been formed at the school and the four follow-ups are the continuation of the learning activities after receiving feedback and input from the team. The procedures carried out must stick to the principles of Arabic learning that already exist.